MOTIVATIONS OF MEXICAN WORKERS TO PARTICIPATE IN CANADA’S SEASONAL AGRICULTURAL WORKERS PROGRAM - Carvajal Gutiérrez, Lidia; Mendoza González, Miguel Ángel; Stallmann, Judith I. (Investigación Económica, 2022)
ABSTRACT This study finds three main motivations for Mexican workers to participate in Canada’s Seasonal Agricultural Workers Program (CSAWP): Increasing household livelihood and welfare, investing in farming skills and assets, and improving children’s education and family housing. A factor analysis and a system of equations are used to find out which sociodemographic and economic characteristics of the migrants and their families are associated with each motivation. The most important results show that having more than four children along with being a farmer are positively associated with investing in farming skills and assets but being an agricultural day laborer in Mexico and having less than two children are not associated with any of the motivations. MOTIVACIONES DE LOS TRABAJADORES MEXICANOS PARA PARTICIPAR EN EL PROGRAMA DE TRABAJADORES AGRÍCOLAS TEMPORALES DE CANADÁ RESUMEN En este estudio identificamos tres motivaciones principales de los trabajadores mexicanos para participar en el Programa de Trabajadores Agrícolas Temporales de Canadá (PTAT): aumentar los medios de subsistencia y el bienestar del hogar, invertir en habilidades y activos agrícolas y mejorar la educación de los niños y la vivienda familiar. Con el análisis factorial y la aplicación de un sistema de ecuaciones vinculamos los tres tipos de motivaciones con las características sociodemográficas y económicas de los migrantes y sus familias. Los resultados más importantes muestran que tener más de cuatro hijos y ser agricultor están asociados positivamente con invertir en habilidades y activos agrícolas, pero ser jornalero agrícola en México y tener menos de dos hijos no están asociados con ninguna de las motivaciones.